Atrial fibrillation as a risk factor for stroke: a retrospective cohort study of hospitalized Medicare beneficiaries. - Yuan, Z (1998)
OBJECTIVES: This study examined the relationship between atrial fibrillation and (1) stroke and (2) all-cause mortality. METHODS: All eligible Medicare patients older than 65 years of age hospitalized in 1985 were followed up for 4 years. Kaplan-Meier and Cox proportional hazards models were used for assessment of risk of stroke and mortality. RESULTS: A total of 4,282,607 eligible Medicare patients were hospitalized in 1985. The mean age was 76.1 (+/- 7.7) years; 58.7% were female; 7.2% were Black; and 8.4% had a diagnosis of atrial fibrillation. During the follow-up period, 66,063 patients (32.6/1000 person-years) developed nonembolic stroke and 7285 (3.6/1000 person-years) developed embolic stroke. After adjustment for age, race, sex, and comorbid conditions, atrial fibrillation remained a significant risk factor for both nonembolic stroke (relative risk [RR] = 1.56) and embolic stroke (RR = 5.80) and for mortality (RR = 1.31). Approximately 4.5% of nonembolic and 28.7% of embolic strokes among hospitalized Medicare patients aged 65 years and older were attributable to atrial fibrillation. CONCLUSIONS: This study demonstrates that atrial fibrillation is associated with an appreciable increase in the risk of stroke (both embolic and nonembolic) and in the risk of mortality from all causes.